Purification and Biochemical Characterization of Asclepain c I from the Latex of Asclepias curassavica L. - Liggieri, Constanza Silvina (2004)
In this work we report the isolation, purification and characterization of a new protease from latex of Asclepias curassavica L. Crude extract (CE) was obtained by gathering latex on 0.1M citric-phosphate buffer with EDTA and cysteine with subsequent ultracentrifugation. Proteolytic assays were made on casein or azocasein as substrates. Caseinolytic activity was completely inhibited by E-64. Stability at different temperatures, optimum pH and ionic strength were evaluated by measuring the residual caseinolytic activity at different times after the incubation. CE showed the highest caseinolytic activity at pH 8.5 in the presence of 12 mM cysteine. CE was purified by cation exchange chromatography (FPLC). Two active fractions, homogeneous by SDS-PAGE, were isolated. The major purified protease (asclepain cI) showed a molecular mass of 23.2 kDa by mass spectrometry and a pI higher than 9.3. The N-terminal sequence showed a high similarity with those of other plant cysteine proteinases. When assayed on N-α-CBZ-aminoacid-p-nitrophenyl esters, the enzyme showed higher preference for the glutamine derivative. Determinations of kinetic parameter (km and Kcat) were performed with PFLNA.